The chalk box kid - Bulla, Clyde Robert; Allen, Thomas B. 1928-. (Thomas Burt). (New York Random House, 1987)
Nine-year-old Gregory's house does not have room for a garden, but he creates a surprising and very different garden in an unusual place.
Keywords: Artists -- Fiction; Imagination -- Fiction; Gardens -- Fiction